Approaches and methods for the study of social media in political communication - Burgess, Jean; Bruns, Axel (Aurora. Revista de Arte, Mídia e Política, 2018)
The role of social media in political communication Given the distributed, multi-platform media environment across which news outlets and citizens alike share and discuss political events, social media are ever-present in contemporary politics. Consequently, the study of social media’s role in political communication is now well-established across media and communication studies, information studies, as well as political science – as is evidenced by the production of multi-disciplinary volumes such as the Routledge Companion to Social Media and Politics (Bruns et al 2016). While researchers in areas like computer-mediated communication (CMC), social network analysis and internet studies were among the first to study social media use (boyd & Ellison, 2007), the political uses and implications of social media are increasingly of interest and concern across the spectrum of social science disciplines. This widespread interest has proceeded alongside the ongoing embedding of social media platforms and practices in the machinery of politics, and the near-ubiquity of social media use among the populations of many nations. However, the specific social media platforms are not ubiquitous, with Facebook and Twitter popular in many parts of the world but irrelevant in China, where social media activity revolves around instant messaging apps like WeChat and, to a lesser extent, the microblogging platform Weibo.